2022
DOI: 10.3390/md20030179
|View full text |Cite
|
Sign up to set email alerts
|

Aurasperone A Inhibits SARS CoV-2 In Vitro: An Integrated In Vitro and In Silico Study

Abstract: Several natural products recovered from a marine-derived Aspergillus niger were tested for their inhibitory activity against SARS CoV-2 in vitro. Aurasperone A (3) was found to inhibit SARS CoV-2 efficiently (IC50 = 12.25 µM) with comparable activity with the positive control remdesivir (IC50 = 10.11 µM). Aurasperone A exerted minimal cytotoxicity on Vero E6 cells (CC50 = 32.36 mM, SI = 2641.5) and it was found to be much safer than remdesivir (CC50 = 415.22 µM, SI = 41.07). To putatively highlight its molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In vitro tests show that natural products are as efficacious as commercially available drugs. The IC 50 values for aurasperone A (12.25 µM) were comparable to those for remdesivir (10.11 µM) [152]. Both have a mechanism of action that inhibits M pro , which is essential for the replication and transcription of SARS-CoV-2 [152].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In vitro tests show that natural products are as efficacious as commercially available drugs. The IC 50 values for aurasperone A (12.25 µM) were comparable to those for remdesivir (10.11 µM) [152]. Both have a mechanism of action that inhibits M pro , which is essential for the replication and transcription of SARS-CoV-2 [152].…”
Section: Discussionmentioning
confidence: 77%
“…The IC 50 result was comparable to the IC 50 of the positive control remdesivir, which was 10.11 µM [152]. The in silico analysis revealed that the molecule aurasperone A targets M pro in SARS-CoV-2 [152]. Furthermore, neoechinulin A isolated from Aspergillus fumigatus MR2012 from the Red Sea exhibited an IC 50 value of 0.47 µM against SARS-CoV-2, with a similar target to M pro [153].…”
Section: Anti-sars-cov-2mentioning
confidence: 72%
See 2 more Smart Citations
“…The data regarding the biological activity of some selected FDA-approved drugs with SARS-CoV-2 M pro has been collected and correlated with our predicted docking score to show the consistency between the calculated binding score and the reported target activities. The activities of Remdesivir (IC 50 = 10.11 μM/L, pIC 50 = 4.995 μM/L) [ 93 , 94 ], Ritonavir: (IC 50 = 13.7 μM/L, pIC 50 = 4.863 μM/L) [ 95 ]; Favipiravir (IC 50 = 9.60, μM/L, pIC 50 = 5.017, μM/L) [ 96 ], and Imatinib: (IC 50 = 3.24, μM/, pIC 50 = 5.489 μM/L) [ 97 ] were compared with the Glide docking score. The resulted coefficient correlation between docking score and biological activity of these drugs has been obtained.…”
Section: Resultsmentioning
confidence: 99%